Neuromuscular electrical stimulation to augment lower limb exercise and mobility in individuals with spastic cerebral palsy: A scoping review - Greve, Kelly R.; Joseph, Christopher F.; Berry, Blake E.; Schadl, Kornel; Rose, Jessica (Frontiers in Physiology, 2022)
Background: Neuromuscular Electrical Stimulation (NMES) is an emerging assistive technology applied as surface stimulation through electrodes placed over the skin or directly to the muscle via implanted electrodes to initiate or augment skeletal muscle contraction. NMES has the potential to improve movement patterns while reducing the neuromuscular impairments of spastic cerebral palsy (CP). This scoping review aimed to examine NMES applications as lower extremity exercises for children with spastic CP, including the effects of NMES on neuromuscular impairments in spastic CP, to provide a foundation of knowledge to advance the field forward and provide more effective treatment. Methods: A literature review of Scopus, Medline, Embase, and Cinahl databases were searched from 2001 to November 2, 2021, using the terms “spastic cerebral palsy” AND “neuromuscular electrical stimulation” OR “functional electrical stimulation”. Results: A total of 168 publications were identified, and an additional 41 were hand-picked from references; 51 articles were duplicates, and 57 articles were discarded due to irrelevant diagnoses or interventions. One hundred one articles met criteria and were thoroughly reviewed by the authors, with 68 additional articles excluded. A total of 33 articles, 26 intervention studies and seven reviews were included in this scoping review. Article topics included the use of NMES for strengthening, assisted gait, and spasticity reduction. NMES-assisted strengthening described the use of therapeutic exercises, including surgical preparation and recovery, and cycling. NMES-assisted gait was applied to improve gait patterns with NMES combined with walking or functional tasks. NMES-spasticity reduction was applied to decrease tone using transcutaneous electrical stimulation parameters or NMES. Conclusions: The application of NMES has been used as an exercise intervention for strengthening, assisted gait, and spasticity reduction for children with spastic CP. Evidence for NMES as an intervention for exercise in children with spastic CP remains limited. Future research should be completed to provide richer evidence to transition to more robust clinical practice.